2002
DOI: 10.1046/j.1523-1755.62.s82.10.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dual blockade of the renin-angiotensin system in primary proteinuric nephropathies

Abstract: Dual blockade of the renin-angiotensin system with ACE inhibitors and AT1 receptor blockers produces a beneficial antiproteinuric effect that could not be explained only by the systemic blood pressure reduction. All treatments were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 28 publications
3
48
0
1
Order By: Relevance
“…The most frequent adverse event has been hyperkalemia, which was managed easily with usual measures and only in rare instances was responsible for study dropout. As expected, this complication was more frequent in patients with reduced GFR (14,25). Some other adverse events, such as hypotension, cough, asthenia, and anemia, also have been reported.…”
Section: Combined Treatment With Acei and Arbsupporting
confidence: 73%
See 2 more Smart Citations
“…The most frequent adverse event has been hyperkalemia, which was managed easily with usual measures and only in rare instances was responsible for study dropout. As expected, this complication was more frequent in patients with reduced GFR (14,25). Some other adverse events, such as hypotension, cough, asthenia, and anemia, also have been reported.…”
Section: Combined Treatment With Acei and Arbsupporting
confidence: 73%
“…BP was reduced significantly from the first month until the end of follow-up for both systolic (SBP) and diastolic BP (DBP) compared with baseline but without any significant difference between groups at any time point. In this study, for the first time, it can be concluded that in chronic proteinuric nondiabetic nephropathies, dual blockade of the RAS with ACEI and ARB produces a beneficial antiproteinuric effect that is not attributable to more pronounced systemic BP reduction (25).…”
Section: Combined Treatment With Acei and Arbmentioning
confidence: 65%
See 1 more Smart Citation
“…In the previously mentioned study of nine patients with nondiabetic renal disease, dual RAS blockade (40 mg lisinopril ϩ 50 -150 mg losartan) induced a significantly greater reduction in proteinuria compared with monoblockade (37). Recently, the combination of ACEI and ARB has also been shown to produce beneficial antiproteinuric effects independent of blood pressure in 45 patients with primary nondiabetic nephropathies followed for 6 months in an open, randomized, paralleled study (44).…”
Section: Dual Ras Blockade Versus Maximal Ace Inhibitionmentioning
confidence: 99%
“…Previously, one of the adverse effects of dual blockade therapy was considered to be hyperkalemia (25). However, the increase in serum potassium levels was thought to be a result of the progression of renal dysfunction, not a complication of add-on therapy.…”
Section: Discussionmentioning
confidence: 99%